JUMPA Vol.4 No.2, Juni 2017 ANALISIS PENGARUH PERSEPSI MAHASISWA PADA UNSUR-UNSUR BAURAN PEMASARAN TERHADAP KEPUTUSAN MAHASISWA MEMILIH PERGURUAN TINGGI IPWIJA PROGRAM S2 (PASCA SARJANA): ANALISIS PENGARUH PERSEPSI MAHASISWA PADA UNSUR-UNSUR BAURAN PEMASARAN TERHADAP KEPUTUSAN MAHASISWA MEMILIH PERGURUAN TINGGI IPWIJA PROGRAM S2 (PASCA SARJANA) - Juli Ismanto IPWI Jakarta (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2017)
The development of the university or college that exist today provide clear evidence that the benefits of their education services not only enjoyed or felt by dealing directly with education services, but also enjoyed by all members of society. Selecting a part of the decision-making process (decision making). Impact determination of choice will be a good influence in the short term and the long term, either in the form of benefits and risks that must be borne. Moreover, the establishment choice in choosing a college is a decision that affects a person's future. Higher education service users (students) can choose many educational alternatives what's right for them, where prospective students pay attention to the educational model and how soon after they graduated from college. In order to further increase public interest in the education services on offer, it is necessary to optimize the marketing management better include education marketing performance, supported by an effective marketing strategy. One step that can be done is to find out the marketing mix variables are most affects students or prospective students as consideration in choosing a university or college. In this study, the variable student's perception on the elements of the marketing mix used to measure students choose college decision IPWIJA S2 program (Post Graduate). The object of this research is that students IPWIJA S2 program (Post Graduate). Quantitative Analysis in the research carried out to test the reliability, validity, classic assumption (consisting of test muultikolineritas, normality test, and test hetrokedasitas), multiple linear regression analysis, goodness of fit test (consisting of the coefficient of determination, F test and t test) , while the qualitative analysis obtained from the interpretation of the respondents. The results showed that the product, pricing, promotion, location, facilities, processes, alumni, reputation, and positive influence on the motivation of the students choose college decision IPWIJA S2 program (Post Graduate).